2013
DOI: 10.1158/0008-5472.can-12-3609-t
|View full text |Cite
|
Sign up to set email alerts
|

xCT Inhibition Depletes CD44v-Expressing Tumor Cells That Are Resistant to EGFR-Targeted Therapy in Head and Neck Squamous Cell Carcinoma

Abstract: The targeting of antioxidant systems that allow stem-like cancer cells to avoid the adverse consequences of oxidative stress might be expected to improve the efficacy of cancer treatment. Here, we show that head and neck squamous cell carcinoma (HNSCC) cells that express variant isoforms of CD44 (CD44v) rely on the activity of the cystine transporter subunit xCT for control of their redox status. xCT inhibition selectively induces apoptosis in CD44v-expressing tumor cells without affecting CD44v-negative diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
178
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(193 citation statements)
references
References 35 publications
(48 reference statements)
10
178
0
1
Order By: Relevance
“…Alternative splicing of exons 6-15 (variant exons 1-10) gives rise to numerous variant forms of CD44 (CD44v), in which an additional segment encoded by one or more of the variant exons is inserted in the extracellular domain of CD44s, which is encoded by exons 1-5 and exons 16-20 (16,42,43). The variant 6 isoform (CD44v6), in particular, is associated with several cancer types but not in somatic cells (15,(18)(19)(20)(21). Moreover, CD44v6 is widely known as a marker of CSCs (18,21,36,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative splicing of exons 6-15 (variant exons 1-10) gives rise to numerous variant forms of CD44 (CD44v), in which an additional segment encoded by one or more of the variant exons is inserted in the extracellular domain of CD44s, which is encoded by exons 1-5 and exons 16-20 (16,42,43). The variant 6 isoform (CD44v6), in particular, is associated with several cancer types but not in somatic cells (15,(18)(19)(20)(21). Moreover, CD44v6 is widely known as a marker of CSCs (18,21,36,(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we estimated that not only the mechanism for the closed margin but also the residual cancer cells after NAC were involved in the mode of local recurrence. Most recently, some researchers reported that these residual cancer cells after NAC possess the characteristics of cancer stem cells (CSC) (14,15). Yoshikawa et al (15) showed that CD44-expressing cancer cells in the clinical samples of human head and neck cancers selectively survive and increase in number after NAC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the expression levels of EGFR, HER2 and HER3 were determined in primary tumors of colorectal cancer cells, and corresponded with lymph node metastases and liver metastases (42,43). The dysregulation of human EGFR pathways by the overexpression or constitutive activation promote s tumor processes, angiogenesis and metastasis in several types of human cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Previous studies have demonstrated that tetrandrine inhibits cell metastasis in 4T1 breast cancer cells (18) and CT26 colorectal cancer cells in vivo (25).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal protein activity and/or expression levels of EGFR have been correlated with the etiology of several types of human cancer, including colorectal cancer (4,5), non-small cell lung cancer (6,7), breast cancer (8,9), head and neck squamous cell carcinoma (10,11), pancreatic cancer (12) and brain cancer (13). EGFR-targeted therapy has been validated in human colorectal cancer (14), and the chemotherapeutics include pharmacological agents, including cetuximab (Erbitux), which is an EGFR inhibitor (15).…”
Section: Introductionmentioning
confidence: 99%